Effect of bone and joint resposition massage on reducing neck pain syndrome in farm workers - Hidayatulah, Muhammad Riyan; Anam, Khaerul (Universitas Hamzanwadi, 2024)
Neck pain is a condition of injury to the soft tissue of the muscles, nerves, blood vessels, lymphatic Neck pain can be caused by several factors, including a sitting position that is too long, the wrong sleeping position, a hard impact on the neck, and pressure on muscles, nerves, bones and joints due to excessive lifting so that muscle stiffness occurs. The aim to be achieved in this study is to determine the effect of repositioning bones and joints (RTS) massage on reducing neck pain (Neck Pain Syndrome) in agricultural workers in Mesanggok Village Kec. Gerung Kab. West Lombok